2023
DOI: 10.1002/adma.202209513
|View full text |Cite
|
Sign up to set email alerts
|

Strongly Correlated Exciton‐Magnetization System for Optical Spin Pumping in CrBr3 and CrI3.

Abstract: Ferromagnetism in van der Waals systems, preserved down to a monolayer limit, attracted attention to a class of materials with general composition CrX3 (X=I, Br, and Cl), which are treated now as canonical 2D ferromagnets. Their diverse magnetic properties, such as different easy axes or varying and controllable character of in‐plane or interlayer ferromagnetic coupling, make them promising candidates for spintronic, photonic, optoelectronic, and other applications. Still, significantly different magneto‐optic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…Simultaneously, the onsite d-d components of the exciton wavefunction are reduced in the ordered AFM phase (Fig. 5f ), leading to a larger oscillator strength 45 , 46 . Together with reduced scattering rates at low temperature, the increased spectral weight from magnetically-induced exciton delocalization allows for robust HEPs in CrSBr.…”
Section: Discussionmentioning
confidence: 98%
“…Simultaneously, the onsite d-d components of the exciton wavefunction are reduced in the ordered AFM phase (Fig. 5f ), leading to a larger oscillator strength 45 , 46 . Together with reduced scattering rates at low temperature, the increased spectral weight from magnetically-induced exciton delocalization allows for robust HEPs in CrSBr.…”
Section: Discussionmentioning
confidence: 98%
“…However, the oscillator strengths of the deepest lying dark exciton only get weakly enhanced in presence of SOC. To put it in perspective, in a purely electronic framework, without considering the impact phonons and defects can have on these excitons, the oscillator strength of the 1.5 eV peak remains at least three orders of magnitude lower than the 1.2 eV exciton in CrI3$_{3}$ [ 22–25 ] and one order lower than the 1.6 eV exciton in NiO [ 26 ] and at least eight orders lower than the exciton in monolayer of MoS 2 . [ 24 ] Interestingly enough, Shin et al [ 1 ] observed a clear photoluminescence peak at 695 nm (1.78 eV) in BAs.…”
Section: Resultsmentioning
confidence: 99%
“…Simultaneously, the onsite d-d components of the exciton wavefunction are reduced in the ordered AFM phase (Fig. 5e), leading to a larger oscillator strength (44)(45). Together with reduced scattering rates at low temperature, the increased spectral weight from magnetically-induced exciton delocalization allows for robust HEPs in CrSBr.…”
Section: Main Textmentioning
confidence: 98%